Mission possible : go create a life that counts - Tebow, Tim, 1987-; Gregory, A. J., 1976- (WaterBrook, 2022)
"Tim Tebow believes that the secret to a truly meaningful life is not more comfort or ease, but recognizing the clear, unique mission that God has set before you. Having a focused sense of your personal, God-given significance will bring you a lasting sense of purpose." -- Amazon.com.